Low dose radiation exposure and cardiovascular diseases: a review - Ling Gao; Chun-Yan Ding (International Journal of Cardiovascular Practice, 2017)
ICRP stated that particular attention should be paid to radiation effects in the cardiovascular system because of recent published observations of radiation effects in this systems occurring after much lower doses than reported previously (ICRP, 2007 and 2012). The review was based on scientific articles available in the open literature, major reviews by other organizations, in particular International Commission on Radiation Protection (ICRP, 118). In this review, we describe low-dose ionizing radiation effect, causes of cardiovascular diseases, relationship between low-dose ionizing radiation and cardiovascular diseases, as well as the importance and urgent of elucidate the relationship between low dose ionizing radiation and cardiovascular disease.